2017
DOI: 10.1038/s41467-017-02223-7
|View full text |Cite
|
Sign up to set email alerts
|

Immune stealth-driven O2 serotype prevalence and potential for therapeutic antibodies against multidrug resistant Klebsiella pneumoniae

Abstract: Emerging multidrug-resistant bacteria are a challenge for modern medicine, but how these pathogens are so successful is not fully understood. Robust antibacterial vaccines have prevented and reduced resistance suggesting a pivotal role for immunity in deterring antibiotic resistance. Here, we show the increased prevalence of Klebsiella pneumoniae lipopolysaccharide O2 serotype strains in all major drug resistance groups correlating with a paucity of anti-O2 antibodies in human B cell repertoires. We identify h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
100
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(111 citation statements)
references
References 53 publications
9
100
2
Order By: Relevance
“…Moreover, optimal killing of ST258 by serum complement occurs in the presence of naturally occurring immunoglobulin G (IgG) (19). In aggregate, those and other previous studies provided support to the idea that immunotherapy (a vaccine approach) can be considered for prevention/treatment of infections caused by carbapenem-resistant K. pneumoniae (20). As a first step toward testing the validity of an immunotherapy approach, we generated antibodies specific for CPS1 and CPS2 of ST258 clinical isolates and tested their ability to enhance serum bactericidal activity and promote phagocytosis and killing by human neutrophils.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Moreover, optimal killing of ST258 by serum complement occurs in the presence of naturally occurring immunoglobulin G (IgG) (19). In aggregate, those and other previous studies provided support to the idea that immunotherapy (a vaccine approach) can be considered for prevention/treatment of infections caused by carbapenem-resistant K. pneumoniae (20). As a first step toward testing the validity of an immunotherapy approach, we generated antibodies specific for CPS1 and CPS2 of ST258 clinical isolates and tested their ability to enhance serum bactericidal activity and promote phagocytosis and killing by human neutrophils.…”
mentioning
confidence: 66%
“…An immunotherapy approach for K. pneumoniae could be extended to target lineages other than ST258, and such work is ongoing (43,44). Moreover, recent studies indicated that antibodies specific for K. pneumoniae lipopolysaccharide work synergistically with antibiotics to improve outcomes in mouse infection models (20). Such an approach could be adapted for use with antibodies specific for CPS or with a combination of antibodies specific for CPS and lipopolysaccharide.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the emergence and global dissemination of extended-spectrum beta-lactamase (ESBL) and carbapenemase producing (CP) clones is a major concern and has led to the recognition of K. pneumoniae as an urgent public health threat (14,15). With the lack of new antimicrobial therapies, there has been a resurgence of interest in alternative strategies such as phage therapy (16)(17)(18)(19), monoclonal antibody therapy (20)(21)(22)(23) and vaccination (24)(25)(26). Several therapeutic targets have been suggested, and the polysaccharide capsule (K antigen) and lipopolysaccharide (O antigen) are among the most frequent.…”
Section: Introductionmentioning
confidence: 99%
“…With only one exception, the key determinants of the O antigenic polysaccharide are co-located at the O locus (previously known as the rfb locus) (36,(40)(41)(42). While 10 serologically distinct O antigens have been recognised, many isolates are non-typeable (23,43) and investigations have identified 12 distinct O loci (25,36). Interestingly, both the O1 and O2 antigens, which are by far the most common (23,25,43), are each associated with the same two loci, O1/O2v1 and O1/O2v2 (25).…”
Section: Introductionmentioning
confidence: 99%
“…Effective vaccination also requires identification of bacterial antigens, their immunogenicity, and the mode of presentation of these antigens -as embedded bacterial antigens in outer membranes or in soluble purified forms, making successful vaccination challenging. New immunotherapies using monoclonal antibodies targeting bacterial antigens are emerging as promising alternatives to passive immunization to tackle antibiotic-resistant bacteria, including K. pneumoniae 4,5 , but often fail to mediate broad protection against different serotypes.…”
Section: Introductionmentioning
confidence: 99%